COVID-19: ramifications of the pandemic on mental health and substance abuse - Munipalli, Bala; Al-Soleiti, Majd; Morris, Anjali; Rummans, Teresa (Frontiers in Public Health, 2024)
Objective: To explore the ramifications of the COVID-19 pandemic on Mental Health and Substance Use. Patients and Methods: Relevant literature examining the correlation between COVID-19 and mental health/substance use was reviewed, and findings were summarized. Results: Specific mechanisms regarding COVID-19's effects on the brain are unclear, but preliminary studies and biomarkers have been suggested in the literature. Numerous studies demonstrated COVID-19 has immediate and lingering neuropsychiatric impacts on affected patients. Psychiatric disorders and substance abuse increased during the COVID-19 pandemic due to biological and psychosocial factors, with a significant burden on individuals and societies worldwide, particularly in the United States. Conclusion: COVID-19 has shown us that underlying causes of mental health and substance abuse problems are more complicated than we have appreciated. Neuroinflammation and psychosocial stresses impact mental health and substance use. These factors need to be explored further for a better understanding and intervention.